Resistance Exercise and Diabetic Foot Exercises on ABI and Blood Glucose Levels in Patients Diabetes Mellitus - Dewi Nur Puspita Sari; Imas Sartika (Sarana Ilmu Indonesia (Salnesia), 2026)
Diabetes Mellitus causes microvascular and macrovascular complications that affect peripheral circulation and blood glucose levels. Resistance exercise and diabetic foot exercises, as non-pharmacological therapies, can improve the Ankle Brachial Index (ABI) and help control blood glucose levels. This study used a quasi-experimental design with a pretest-posttest control group design. The population consisted of all Diabetes Mellitus patients at Puskesmas Jati Uwung. A total of 60 subjects were selected using purposive sampling. Statistical tests included the Wilcoxon signed-rank test, Mann–Whitney test, and General Linear Model. The Mann–Whitney test results showed that resistance exercise and diabetic foot exercises had a significant effect on the Ankle Brachial Index (ABI) (p = 0.001). The mean blood glucose level in the intervention group decreased from 259 mg/dL to 183 mg/dL (76 mg/dL), while the control group decreased from 257 mg/dL to 182 mg/dL (75 mg/dL). These findings indicated that the intervention helped improve peripheral circulation and reduce blood glucose levels in patients with Diabetes Mellitus. In conclusion, resistance exercise was found to be an effective, safe, and comfortable physical exercise intervention to improve ABI and blood glucose levels independently in patients with Diabetes Mellitus.